PENTINGNYA SISTEM KOMPENSASI YANG BERSIFAT ADIL SERTA LAYAK DALAM UPAYA PENINGKATAN KINERJA PADA KARYAWAN - Yuni Setyawati (Unitri Press, 2020)
This research illustrates the importance of providing fair and appropriate compensation and analyzes the relationship between compensation and the performance of the employees of PO Bis Akas II NNR Medaeng Sidoarjo. This qualitative descriptive research selects sources or informants by purposive. Data were collected based on observations, in-depth interviews, documentation collection and literature review. This study seeks to describe and interpret research data by comparing research data with related theories. The application of compensation in PO Bis Akas II NNR Medaeng included financial compensation (salary / wages, benefits, incentives) and non-financial (work environment, responsibility and promotion). The payment system and the size of the amount of compensation paid to employees is adjusted to the level of work. The existence of fair and proper compensation is trying to be applied by PO Bis Akas II NNR Medaeng and must be felt and in accordance with employee expectations. If this can be fulfilled, then the employee will feel satisfied and encourage to work harder and be responsible for doing work and certainly will have better performance that is getting better in quality, quantity side and work completed on time.